Children's drawing as a measurement of dental anxiety in paediatric dentistry - HAZNEDAROĞLU, EDA (WILEY, 2020)
Background Drawings can be used as a method of communication that represents an individual's self-concept, anxiety, attitude or conflict. Aim The purpose of this study was to evaluate children's drawing as a measure of dental anxiety in a dental setting. Design Seventy-eight children, aged 6-12 years, were enrolled in this study. Pulp therapy and/or restorative treatment was performed during the first therapeutic session for all participants. Sound, Eye and Motor (SEM) and Frankl scales were used as an objective assessment of behaviour during treatment. After the treatment session, the children were instructed to draw a picture of a person at a dental clinic. Children's drawings were scored by a paediatric dentist and a psychologist using Child Drawing: Hospital (CD: H) scale and emotional indicators of Human Figure Drawings (HFD). The findings were compared with Frankl and SEM scores. Results There was a significant negative correlation between Frankl and CD: H scores (P = .017), and a significant negative correlation was found between HFD and Frankl scores (P = .048). Conclusion Drawings can reveal a considerable amount of information about children's emotional status, and children's drawing can be a useful non-verbal self-report measure to evaluate anxiety in a paediatric dental setting.
Keywords: children; dental anxiety; drawing; FEAR